Gestión administrativa y financiera de los servicios exequiales de la ciudad de Babahoyo, provincia de los Ríos. - VILLACRES VERA, PABLO (2015)
The main objective of this thesis is framed in the development of a pre-feasibility study for the creation of a new municipal cemetery for the city of Babahoyo, is an initiative from the aims, intended to provide an alternative the discontented population, where the only objective will be to provide funeral service with high quality standards, similar to that of private organizations engaged in this business services. The current municipal cemetery of Babahoyo has collapsed, due to its physical space does not allow keep getting more bodies, because increasing use-space that is occurring is the reduction of mobility in it, caused by constructions made up of existing or small passageways tombs there.